2015
DOI: 10.3986/ags.747
|View full text |Cite
|
Sign up to set email alerts
|

European capital of culture: residents' perception of social benefits and costs – Maribor 2012 case study

Abstract: This study assessed Maribor residents' attitudes towards social impacts of the European capital of culture, using FSIAS scale. The results showed that residents perceived more social benefits than social costs of the event. They agreed that the event had positive impacts primary on the promotion of Slovenia, as well as on community cultural life and image in general, which is also consistent with the purpose and the aims of the event. In residents' opinion the event did not cause any negative impacts. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…For Jorgensen (2015), an artist can be an »interlocutor for social change,« and for Markusen and Gadwa (2010) also a substantial contributor to the ascent of the cultural industry. It is due to its catalytic potential that art is often integrated in urban revitalization programs through initiatives on various scales -from flagship, prestige and internationally renowned projects to smaller communal revitalization initiatives (Hall and Robertson 2001;Dragićević et al 2015;Rembeza 2016). Gastronomy and food have been recognized as catalysts as well: catalysts for improved cultural understanding (Santich 2007) and economic development, especially tourism (van Westering 1999), the food industry (Richards 2002) and the creative industry (Hurtado Justiniano et al 2018).…”
Section: Role Of Art In Creative Place-makingmentioning
confidence: 99%
“…For Jorgensen (2015), an artist can be an »interlocutor for social change,« and for Markusen and Gadwa (2010) also a substantial contributor to the ascent of the cultural industry. It is due to its catalytic potential that art is often integrated in urban revitalization programs through initiatives on various scales -from flagship, prestige and internationally renowned projects to smaller communal revitalization initiatives (Hall and Robertson 2001;Dragićević et al 2015;Rembeza 2016). Gastronomy and food have been recognized as catalysts as well: catalysts for improved cultural understanding (Santich 2007) and economic development, especially tourism (van Westering 1999), the food industry (Richards 2002) and the creative industry (Hurtado Justiniano et al 2018).…”
Section: Role Of Art In Creative Place-makingmentioning
confidence: 99%
“…There is no doubt that the economic impacts of festivals are important, but the social impacts may have an even more profound effect upon the local community's everyday life (Delamere 1998;Fredline et al 2003). However, recently there has been growing interest in studying the non-economic impacts of the events on residents in academic circles (Arcodia and Whitford 2006;Bagiran and Kurgun 2013;Dragićević et al 2015;Loots et al 2011;Robertson and Wardrop 2012). In this respect, Deery and Jago (2010) stated that understanding the social and environmental impacts of events became both a practitioner and academic priority.…”
Section: Impacts Of Events On Local Communitymentioning
confidence: 99%
“…Events are one of the fastest growing segments of tourism industry that yield profound impacts on economy, environment and society at the individual level, the community level, and the regional level. (Arcodia and Whitford 2006;Bagiran and Kurgun 2013;Dragićević et al 2015;Getz 1997;Loots et al 2011;McDonnell et al 1999). Since festivals are not dependant on the natural resources and cultural heritage of the destination, they can be developed more easily than other forms of travel and tourism.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research on the ECoC event that includes host city residents' perceptions and associations has commonly focused on the event's social benefits (e.g. Dragi cevi c et al, 2015;Liu, 2016;Van der Steen and Richards, 2021; Zili c Fi ser and Ko zuh, 2019) and cities' branding and images (e.g. Farmaki et al, 2019;Kova ci c et al, 2021;Liu, 2015;Richards and Wilson, 2004;Shukla et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is evident that the social impacts of the event were mainly discussed, while other types of impacts, including economic or environmental impacts, remained neglected. Considering the relevant literature on local people's perception of the ECoC event's social aspect, authors have shown that among the most highly perceived social benefits of the event are the promotion of the host country (Dragi cevi c et al, 2015), increased quality of life, enhanced image and cultural legacies (Liu, 2016) and development of a sense of community pride ( Zili c Fi ser and Ko zuh, 2019). However, after reviewing existing IJEFM 13,2 literature on the ECoC event, the need to investigate residents' perception of all three aspects of the event's sustainability has emerged.…”
Section: Introductionmentioning
confidence: 99%